1997
DOI: 10.1557/jmr.1997.0057
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles of Ag, Au, Pd, and Cu produced by alcohol reduction of the salts

Abstract: Nanoparticles of Ag, Au, Pd, and Cu have been prepared by the reduction of their salts by ethyl alcohol under refluxing conditions in the presence of polyvinylpyrrolidone (PVP). In the case of Au and Cu, it was necessary to use magnesium metal as a catalyst during the reduction. The nanoparticles are in the 5-35 nm range in the case of Ag, Au, and Pd, but there is considerable agglomeration in the case of Cu even in the presence of PVP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
106
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(111 citation statements)
references
References 9 publications
3
106
0
Order By: Relevance
“…Absorbance was taken in UV-spectrometer in different time intervals with both the isolates in the particular wavelengths where they have shown higher activity in silver nanoparticles and ZnO nanoparticles production. Both the graphs showed an increase in absorbance in various time intervals (0, 6,12,18,24,30,36,42, and 48 hrs) (Figs. 7 and 8).…”
Section: Uv-spectrometer Analysis Of Silver and Zno Nanoparticlesmentioning
confidence: 95%
See 1 more Smart Citation
“…Absorbance was taken in UV-spectrometer in different time intervals with both the isolates in the particular wavelengths where they have shown higher activity in silver nanoparticles and ZnO nanoparticles production. Both the graphs showed an increase in absorbance in various time intervals (0, 6,12,18,24,30,36,42, and 48 hrs) (Figs. 7 and 8).…”
Section: Uv-spectrometer Analysis Of Silver and Zno Nanoparticlesmentioning
confidence: 95%
“…Recent studies have shown that nanoparticle from some materials such as metal oxides are capable of inducing eukaryotic cell death and in prokaryotic, cell growth is inhibited by its cytotoxic effect [5]. Nanoparticles can be synthesized by different methods involving physical methods, chemical methods, and biological methods [6]. In recent years, the demand to develop eco-friendly procedures with low cost and non-toxic methods for nanoparticle synthesis is increased [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The NCC may participate in the reduction reaction by the electron transfer from OH À to high valence state metal species (Sawyer and Roberts, 1988;Shin et al, 1987;Ayyappan et al, 1997). However, the reduction ability of SCM could be weakened in the presence of oxidizing species such as high valence state Fe in the reaction system (Fe in PCBs can be oxidized to their high valence state in dilute nitric acid pretreatment).…”
Section: Effect Of Ferric Irons Contained In the Second Leach Liquor mentioning
confidence: 99%
“…The ferric iron can weaken the reduction ability of SCM system, leading to that the reducing power of SCM is not enough to reduce all of cupric ions to zero-valent copper, so some cuprous oxides were formed. The possible reaction is as follows: In SCM system, the NCC (OH À ) can act as a reductant by the electron transfer from OH À to metal ions (Sawyer and Roberts, 1988;Shin et al, 1987;Ayyappan et al, 1997). According to the reaction Eqs.…”
Section: Effect Of Ferric Irons Contained In the Second Leach Liquor mentioning
confidence: 99%
“…2,3 Other simple methods involve reducing metallic salts by the solvent used to prepare colloidal dispersions. [4][5][6][7][8][9] Hydrogen reduction techniques represent some of the simplest ways to obtain colloidal dispersions because they require a minimum number of components, thus avoiding the need for an undesirable excess of the reducing agent and the formation of reaction byproducts. 10 However, hydrazine reduction method offers the advantages of being able to produce the essentially also clean silver particles, which contains no inorganic ions except amine, carbon dioxide and nitrogen, even at room temperature.…”
Section: Introductionmentioning
confidence: 99%